An Using E-CRM To Improve Market Value Companies - Ruri Koesliandana; Arnes Yuli Vandika; Dina Ika Wahyuningsih (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
E-Customer relationship management can help organizations manage customer interactions more effectively to maintain competitiveness in the present economy. As more and more organizations realize the significance of becoming customer-centric in today’s competitive era, they adopted E-CRM as a core business strategy and invested heavily.E- CRM, an integration of information technology and relationship marketing, provides the infrastructure that facilitates long-term relationship building with customers at an enterprise-wide level. Successful E-CRM implementation is a complex, expensive and rarely technical projects. This paper presents the successful implementation of E-CRM from process perspective in a trans-national organization with operations in different segments. This study will aid in understanding transition, constraints and the implementation process of E-CRM in such organizations.